HUBUNGAN DUKUNGAN SOSIAL DENGAN PENGGUNAAN PENGOBATAN ALTERNATIF BEKAM PADA PASIEN HIPERTENSI - Vidia Humaira; Bayhakki Bayhakki; Wan Nishfa Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Social support is one of several factors use of cupping treatment in hypertension patients. This study aims to determine the relation between social support and use of cupping treatment in hypertension patients. This research was using descriptive correlation design with cross sectional method. A total of 53 sample using total sampling technique. The instrument used was a questionnaire. The data analysis used was the chi-square test. This research found that most of the patients are middle-age adults, it is about 33 person (62,3%), female gender 32 person (60,4%), university graduate 29 person (54,7%), housewife 23 person (43,4%). The results of the use statistical test found that there was a significant relation between social support with alternative cupping treatment in hypertension patients (p value 0,008; alpha 0,05). Based on the research, it is hoped that the public, especially hypertension patients can use cupping therapy as a way to treat their disease.Keywords: Cupping, social support, hypertension